Kontribusi K.H. Muhammad Amin Azhari dalam Menyebarkan Agama Islam melalui Pendidikan di Madrasah Ibtidaiyah Najahiyah Palembang - Heryati, Heryati; Rusdiana, Yusinta Tia; Damayanti, Selvina (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2024)
This research was motivated by the author's desire to know the contribution of K.H. Muhammad Amin Azhari in spreading Islam through education at Madrasah Ibtidaiyah Najahiyah. This research method is a qualitative research method. The type of research is descriptive qualitative with a historical approach. The data collection process is observation, interviews, documentation and literature study. The data analysis technique is using data reduction, data presentation, and conclusions (1) The history of the founding of the Najahiyah Ibtidaiyah Madrasah is that this madrasah was a madrasah endowed by the Palembang cleric, namely K.H. Muhammad Amin Azhari to spread Islam through education (2) Contribution of K.H. Muhammad Amin Azhari in spreading Islam through education, namely after he donated his land to build the Najahiyah madrasah, after the establishment of this madrasah, he participated in teaching religious sciences, such as Tauhid and Fiqh (3) The existence of the Najahiyah Madrasah had a positive impact on the people of Palembang, especially in the upper 3-4 regions in the socio-religious, socio-cultural and socio-economic fields, it is still around.